The rights revolution revisited : institutional perspectives on the private enforcement of civil rights in the US / edited by Lynda G. Dodd. - Dodd, Lynda G., 1968- (Cambridge University Press, 2018)
The rights revolution in the United States consisted of both sweeping changes in constitutional doctrines and landmark legislative reform, followed by decades of innovative implementation in every branch of the federal government - Congress, agencies, and the courts. In recent years, a growing number of political scientists have sought to integrate studies of the rights revolution into accounts of the contemporary American state. In The Rights Revolution Revisited, a distinguished group of political scientists and legal scholars explore the institutional dynamics, scope, and durability of the rights revolution. By offering an inter-branch analysis of the development of civil rights laws and policies that features the role of private enforcement, this volume enriches our understanding of the rise of the 'civil rights state' and its fate in the current era.